2021
DOI: 10.4239/wjd.v12.i9.1401
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of type 2 diabetes in the Middle East and North Africa: Challenges and call for action

Abstract: Type 2 diabetes continues to be a serious and highly prevalent public health problem worldwide. In 2019, the highest prevalence of diabetes in the world at 12.2%, with its associated morbidity and mortality, was found in the Middle East and North Africa region. In addition to a genetic predisposition in its population, evidence suggests that obesity, physical inactivity, urbanization, and poor nutritional habits have contributed to the high prevalence of diabetes and prediabetes in the region. These risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 116 publications
4
44
1
Order By: Relevance
“…Additionally, obesity is also associated with the increasing incidence of related metabolic disorders such as type 2 diabetes (T2D), which can raise the risk of cardiovascular disease by twofold [ 3 ]. The Middle East and North Africa region carried the highest prevalence of diabetes in 2019 at 12.2%, with a predicted 30% obese by 2030 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, obesity is also associated with the increasing incidence of related metabolic disorders such as type 2 diabetes (T2D), which can raise the risk of cardiovascular disease by twofold [ 3 ]. The Middle East and North Africa region carried the highest prevalence of diabetes in 2019 at 12.2%, with a predicted 30% obese by 2030 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetes among individuals aged 25-65 was 8.4% in 2004 and increased to 13.2% in 2016, which was higher than the worldwide average projected by International Diabetes Federation for 2017(8.4%) [ 21 ]. Similar to other countries located in the MENA region, Iran has witness an increasing trend in recent years, contributed by different factors including genetics, obesity, physical inactivity, urbanization, and poor nutritional habits [ 22 , 23 ]. In line with the present study, the prevalence of diabetes in most similar national studies was reported to be increasing, ranging from 7.4 to 24.5% [ 24 – 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors and diseases place enormous pressures on the health system and resources; therefore, they require significant policy attention. For example, the MENA region experienced the highest global increase in the prevalence of diabetes mellitus in 2019 (12.2% of the adult population aged 20–79 years) and is expected to witness the second-highest increase (96%) in this prevalence between 2019 and 2045 compared to other parts of the world [ 88 ] . Similarly, a recently published review article indicated that the overall estimated pooled prevalence of hypertension in MENA was 26% and is estimated to double by 2025 [ 89 ] .…”
Section: Discussionmentioning
confidence: 99%